COMPARATIVE ASSESSMENT OF SOME MINERALS IN SOIL, FORAGE AND SHEEP SERUM IN TWO REGIONS IN THI-QAR PROVINCE - Aamir M. Abed Al-Ghareebawi (Basrah Journal of Veterinary Research)
The objective of this investigation is to evaluate the level of the some minerals (sodium, potassium and calcium) in the soil, forage and sheep serum, the specimens were 1 Kg of soil and forage and 10 blood samples taken from each district (Nasriya and Shatra) in Thi-Qar province. The results show that significant (p≤0.05) increase in the sheep serum sodium concentration in Nasriya region (44.21±14.9) Mmol/L compared with the Shatra (34.84±6.61) Mmol/L, while the potassium concentration in sheep serum appeared a significant (p≤0.05) decrease in Nasriya district (6.23±1.00) Mmol/L compared with Shatra(13.16±2.42) Mmol/L but there is no significance (p≤0.05) change found in sheep serum calcium between the two studied areas in Nasryia was (0.40±0.12) Mg/dl but Shatra was (0.24±0.05) Mg/dl. The sodium level in the forages is high but not significant(p≤0.05) in the Nasriya(0.369±0.101)when compared with Shatra(0.321±0.011) g/Kg The potassium in forages is higher in Nasriya (0.411±0.011) g/Kg but not significant (p≤0.05) when compared with Shatra (0.255±0.011) g/Kg Calcium of forage was decreased in Nasryia (0.136±0.012) g/Kg but in Shatra was (0.355±0.044) g/Kg with no significancy (p≤0.05). In soil sodium of Nasryia is high (0.942±0.051) g/Kg but not significant (p≤0.05) and in Shatra was (0.887±0.032) g/Kg, the potassium in soil of Nasryia was (0.418±0.023) g/Kg but not significant (p≤0.05) and in Shatra was(0.424±0.022) g/Kg Calcium is higher in Nasriya soil (0.602±0.043) g/Kg but lower in soil of Shatra was (0.657±0.048) g/Kg with no significancy (p≤0.05).